Relationship between knowledge, attitudes and Oral health practices of parents with caries early childhood of children with anemia of the Recuay community - Sihuay Torres, Kamila (2021)
Early childhood caries affects more than 60% of children in Peru, affecting their quality of life and diet. It is important to know the knowledge, attitudes and practices in oral health of the caregivers of these children to perform appropriate intervention strategies. Objective: Relate the knowledge, attitudes and practices in oral health of parents with the early childhood caries of children with anemia in the community of Recuay. Materials and methods: Relational level study, quantitative approach, observational, cross-sectional and prospective design. 52 children from 0 to 6 years old diagnosed with anemia and their parents participated. The ceo-d index and the simplified oral hygiene index (IHO-S) were applied to the children; and a questionnaire of knowledge, attitudes and practices in oral health to their parents. The ceo-d and IHO-S index was related to the level of knowledge, attitudes and practices using Spearman's correlation coefficient. Results: It was found that 69% of children have early childhood caries, the average ceo-d index was 3.3, which increased with age. The average IHO-S was 1.95. The level of knowledge, attitudes and practices of the parents was regular, adequate and regular respectively. Spearman's correlation coefficient between oral health practices and the ceo-d index was 0.375 (p <0.05).